Stigma and Associated Correlates of Elderly Patients With Parkinson's Disease - Hou, Miaomiao; Mao, Xiaowei; Hou, Xiaojun; Li, Kunpeng (Frontiers in Psychiatry, 2021)
Background: Stigmatizing experiences is common in Parkinson's disease (PD) and appears to provide a negative contribution to the quality of life. Our aim of this study was to investigate the extent of stigma and its predictive factors in patients with PD from our hospital in Shanghai, China. Methods: In 276 individuals with PD (135 women and 141 men), stigma was measured by the 24-item Stigma Scale for Chronic Illness (SSCI). Multivariate linear regression model was used to assess predictors of stigma including demographics (age and gender), disease duration, stage (Hoehn and Yahr Scale), motor function (Unified Parkinson's Disease Rating Scale Part 3, UPDRS-III), non-motor symptoms (Non-Motor Symptoms Scale, NMSS), cognitive level (Mini-Mental State Examination, MMSE), as well as anxiety (Hamilton Anxiety Rating Scale, HAM-A) and depressive disorders (Hamilton Depression Rating Scale, HAM-D-24). Results: The total score of SSCI was 49.9 ± 14.3, and 48.5% of the patients checked “rarely” to “sometimes.” For the total sample, the full model accounted for 47.8% of the variance in stigma (P < 0.05). Higher UPDRS-III scores, longer course of disease, younger age, tremor-dominant subtype, and higher depression scores were significantly associated with stigma among individuals with PD. Conclusion: Our finding suggested a mild-to-moderate level of stigma in patients with PD. Tremor-dominant subtype, longer course of disease, younger age, severe motor symptoms, and depression are the predictors of stigma in PD.